Traffic modelling for ethernet passive optical network using MATLAB - Radzi N.A.M.; Din N.M.; Sadon S.K.; Al-Mansoori M.H.; Abidin H.Z. (IEEE Computer Society, 2023)
Ethernet Passive Optical Network (EPON) has gained the interest of many researchers nowadays as it is one of the best technologies to overcome congestion in the local loop between the customer and local exchange. Many network simulators exist in order to study EPON, but the simplest method to study EPON is using MATLAB. However, in order to study EPON using MATLAB, the traffics need to be generated as according to Ethernet traffic to avoid an impairment in the network design. This paper proposes a traffic modeling in MATLAB based on the source code obtained in NS-2 so that it can be used as a discrete event simulator for EPON. The results obtained show that the traffic generated is in line with the results generated in NS-2; and hence valid to be used in EPON. 2013 IEEE.